Copper oxide nanoparticles synthesized from Trichosanthes kirilowii ameliorates the DSS-induced acute colitis in mice through the suppression of inflammatory responses - Xuefeng Jiang; Yu Sun; Tahani Awad Alahmadi; Velu Manikandan; Thamaraiselvan Rengarajan; Yuyang Zhao (Journal of King Saud University: Science, 2022)
Introduction: Ulcerative colitis (UC) is chronic inflammatory ailment that distinguished by diarrhea, stomach pain, reduced body weight, and hematochezia. UC affects nearly 400 per 100,000 peoples worldwide. In this exploration, we intended to fabricate the copper oxide nanoparticles from the T. kirilowii (TK-CuNPs) and inspect their curative potential against the Dextran sulfate disodium salt (DSS)-provoked colitis in animals. Methods: Formulated TK-CuNPs were characterized by UV–vis spectroscopy, FT-IR, SEM, TEM, and DLS techniques. UC was provoked in mice through administering of 2% DSS for 7-days and treated with the 10 mg/kg bodyweight of TK-CuNPs via intragastric intubation. Myeloperoxidase activity, colon weight, and length, and spleen weight were determined by standard methods. Pro-inflammatory mediators, i.e. IL-6, IL-1β, and TNF-α were inspected by the assay kits. The expression of COX-2 and iNOS were analyzed by immunohistochemistry. Histopathological changes in colon tissues were investigated microscopically by H&E staining. The cytotoxicity and in vitro anti-inflammatory activities of TK-CuNPs were analyzed in RAW-264.7 cells. Results: The outcomes of various characterization studies demonstrated the formation of TK-CuNPs. The TK-CuNPs supplementation to the DSS induced colitis mice demonstrated the appreciable bodyweight gain and reduced the DAI scores. TK-CuNPs improved the colon length and spleen weight and suppressed the MPO activity. The status of pro-inflammatory mediators IL-6, IL-1β, and TNF-α was appreciably suppressed by the TK-CuNPs treatment. The expressions of COX-2 and iNOS was also diminished by the TK-CuNPs. TK-CuNPs did not possessed toxicity to the RAW-264.7 cells and suppressed the inflammatory markers level in the RAW-264.7 cells. Discussion and Conclusion: The current findings revealed that fabricated TK-CuNPs can be a hopeful therapeutic agent to treat acute colitis.